Menanamkan Kompetensi Profesional dan Budaya Belajar Melalui Penerapan Pembelajaran dengan Metode Information Search pada Mata Kuliah Analisis Vektor - Wasilatul Murtafiah (Jurnal Penelitian Pendidikan, 2013)
This study aims at inculcating Professional Competence and Cultural Learning Through Learning implementation using Information Search Method in the Vector Analysis Subject. This study uses the mechanism and design of learning software development according to Fenrich (2007). The data collection techniques that are used are: observation, test and questionnaire. The data analysis techniques are by using quantitative and qualitative descriptive analysis ( mixing method). The subject of this study is 39 students of sixth semester of academic year 2012/2013 Mathematic study program of IKIP PGRI MADIUN. The results shows that: (1) learning by using information search method in the Vector Analysis subject to inculcate a culture of learning and professional competence of students developed include: lesson plans, LKM, and THB with good and excellent category making it feasible to use, (2) Attainment Level of students’ professional competence through information search learning method in the Vector Analysis subject has not met the predetermined criteria. There are approximately 58.97 % of students who pass the study, it means that the professional competence has not been achieved because the number of students who pass the study are less than 75 % of the total number of students, (3) The attainment level of student learning culture through the information search method in the Vector Analysis subject is obtained satisfactorily and very good criteria with a percentage of more than 75 %.